Formulation Of Social Media Content Strategy For BabyRaf Jakarta to Increase Revenue Growth - Delanny Dwi Nugrahini Sani; Nila Armelia Windasari (Journal of Economics and Business UBS, 2023)
BabyRaf Jakarta is a company engaged in the rental of children's toys and baby needs from birth to 8 years old. This company was founded in 2018. From the beginning until the end of 2021, the company experienced an increase in revenue. Even during the initial conditions of the pandemic. However, at the beginning of 2022, the trend of fluctuating income tends to decrease. As an effort to improve company performance, BabyRaf Jakarta is trying to focus on attracting customers according to its target market. Companies use social media Instagram to increase customer awareness. The company has a social media strategy, namely displaying several 4 types of content that are distributed through Instagram ads. After evaluation, the strategy is less than optimal in attracting customer interest to use products from BabyRaf. With the problem of social media owned by BabyRaf Jakarta, the author conducted various analyzes and then formulated a marketing strategy through social media Instagram, namely prioritizing the use of content that contains a portfolio of products and prices as well as informational content and its implementation. The analysis used is competitor analysis and root cause analysis. Competitor analysis aims to examine products, sales and marketing strategies of competitors from BabyRaf Jakarta. Meanwhile, Root Cause Analysis aims to identify the root causes of BabyRaf Jakarta's social media problems that are not performing well. The next step is to conduct a survey to find out the preferences of potential and existing customers in their interest in choosing Instagram content. There are 4 types of content studied, namely Informational Content, Product Portfolio & Price Content, Review Customer Content, and Promo & Discount Content. The survey results were processed quantitatively and analyzed using the Independent Sample T-test and ANOVA calculations. Based on the survey results, customers are more interested in the two types of content, namely Informational Content and Product Portfolio & Price Content. The solution to these problems is listed in the implementation plan which is outlined in the content schedule. In the content schedule, the content that is most in demand by customers according to the survey results, has more broadcast schedules than other types of content. Then, social media content recommendations are made as strategy implementation content.